Kant's categorical imperative : an analysis of the first set of Grundlegung illustrations - Baigrie, D. J.(Diarmuid James) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1978.